Analysis of procalcitonin and urine nitrite to predictor sepsis patients - Maghfirah, Andi Itha; Muhiddin, Rachmawati; Handayani, Irda; Kadir, Nursin Abdul (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2021)
Background: Sepsis is a significant health problem worldwide. Various sepsis biomarkers have been studied before, but few data link PCT and urinary nitrite levels to culture result in septic patients. Purposes: This study compares PCT, Urine Nitrite on culture results against their sensitivity to determine variables that can be used to predict sepsis patients. Methods: This is a cross-sectional study by taking data on patients with sepsis aged â‰¥18 years in 207. Diagnostic tests were performed to determine sensitivity and specificity of PCT, Urine Nitrite, and Blood Culture of septic patients. A Chi-square test was carried out to see the relationship between two parameters and the outcome of sepsis. Results: PCT sensitivity was higher than Urine Nitrite: 74.5%. Specificity of Urine Nitrite was higher than PCT: 88.2%. Procalcitonin has a significant relationship with sepsis patient outcomes (p<0.005). Conclusion: PCT can predict septic patients because it has a higher sensitivity than urine nitrite